Bahasa Indonesia: Bahasa Indonesia - Sebayang, Melya Dyanasari; Samosir, Rahmad; Budiarto, Budiarto; Sihite, Edward Baringin; Saragih, Riswanton; Simorangkir , Melda (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
In connection with the easing of the Covid 19 virus in Indonesia, the Indonesian Christian University (UKI) Engineering PKM TEAM conducted welding training offline for children with special needs. The purpose of the Service for children at the Panti Karya is to be able to provide training in welding and making trash cans easily and effectively as life skills for the children of the HEPHATA HKBP Panti Karya Foundation in North Sumatra Participants, to be able to implement cleanliness around the Hephata HKBP Panti Karya Foundation in North Sumatra as well as children who already have the skills to make trash cans from welding training can generate incoming funds for the HKBP Hephata Panti Foundation in North Sumatra. With this dedication, we can equip the children of the Karya Orphanage with life skills in making trash cans and welding to increase their competence.